2002
DOI: 10.1074/jbc.m200338200
|View full text |Cite
|
Sign up to set email alerts
|

The 7472insC Mitochondrial DNA Mutation Impairs the Synthesis and Extent of Aminoacylation of tRNASer(UCN) but Not Its Structure or Rate of Turnover

Abstract: The 7472insC mitochondrial DNA mutation in the tRNA Ser(UCN) gene is associated with sensorineural deafness combined, in some patients, with a wider neurological syndrome. In cultured cybrid cells it causes a 70% decrease in tRNA Ser(UCN) abundance and mild respiratory impairment, previously suggested to be due to decreased tRNA stability. When mitochondrial transcription was blocked by ethidium bromide treatment, the half-life of the mutant tRNA was not significantly different from that of wild-type tRNA Ser(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
39
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 58 publications
4
39
1
Order By: Relevance
“…Diseases associated with hmt-tRNA point mutations include MERRF (myoclonic epilepsy with ragged red fibers), MELAS (mitochondrial myopathy, encephalopathy, lactic acidosis, and stroke-like episodes), and deafness (2)(3)(4). Pathogenic mutations of hmt-tRNAs have been shown to affect global tRNA structure (5)(6)(7)(8), tRNA processing (9-13), modification (14)(15)(16)(17)(18)(19)(20), aminoacylation (7,(21)(22)(23)(24)(25)(26), and translation efficiency (27)(28)(29). However, little is known about the precise pathogenic mechanisms of the vast majority of hmt-tRNA mutations, hindering the development of appropriate treatments.…”
mentioning
confidence: 99%
“…Diseases associated with hmt-tRNA point mutations include MERRF (myoclonic epilepsy with ragged red fibers), MELAS (mitochondrial myopathy, encephalopathy, lactic acidosis, and stroke-like episodes), and deafness (2)(3)(4). Pathogenic mutations of hmt-tRNAs have been shown to affect global tRNA structure (5)(6)(7)(8), tRNA processing (9-13), modification (14)(15)(16)(17)(18)(19)(20), aminoacylation (7,(21)(22)(23)(24)(25)(26), and translation efficiency (27)(28)(29). However, little is known about the precise pathogenic mechanisms of the vast majority of hmt-tRNA mutations, hindering the development of appropriate treatments.…”
mentioning
confidence: 99%
“…Multiple abnormal tRNA Ser (UCN) signals in the patient's samples suggested the presence of incompletely processed forms of the tRNA. A severe structural defect of the mutant tRNA may make it primarily unstable, or prevent binding to the mitochondrial seryl-tRNA synthetase, leading to degradation of unaminoacylated tRNA (18)(19)(20). The dramatic lack of a specific tRNA explains the severe RC deficiency, leading to uncontrolled lactic acidosis and rapid progression to fatality from the disease in this infant.…”
Section: Discussionmentioning
confidence: 99%
“…Biochemical data showed that cell lines carrying this mutation produced a significant decrease in the level of this tRNA, which was combined with a small but clear decrease in the extent of aminoacylation. Only very subtle effects on structure or stability were found [89,90].…”
Section: Mitochondrial Trna Mutations Associated With Nonsyndromic Hementioning
confidence: 99%